The head beneath the altar : Hindu mythology and the critique of sacrifice - Collins, Brian (Brian H.) (Studies in violence, mimesis, and culture., 2014)
In the beginning, says the ancient Hindu text the Rg Veda, was man. And from man's sacrifice and dismemberment came the entire world, including the hierarchical ordering of human society. The Head Beneath the Altar is the first book to present a wide-ranging study of Hindu texts read through the lens of René Girard's mimetic theory of the sacrificial origin of religion and culture. For those interested in Girard and comparative religion, the book also performs a careful reading of Girard's work, drawing connections between his thought and the work of theorists like Georges Dumézil and Giorgio.